DEMENTIA FAMILY CAREGIVERS EXPERIENCES USING COMMUNITY-BASED AND HEALTHCARE SERVICES DURING COVID-19. (20th December 2022) - Leggett, Amanda; Baker, Elaina; Lee, Hannah; Webber, Anna; Wallace, Sarah; Fang, Tyson; Johnson, Florence
Abstract: Family caregivers are key medical decision makers for persons living with dementia (PLwD) and play a critical role in interfacing with community-based services and the health care system. The COVID-19 pandemic, however, had dramatic impact on service utilization, with many suspended, delayed, or moved to telehealth. Emerging data suggests the pandemic posed challenges to service use for family caregivers, yet how this impacted caregiver's care practice is unknown. An in-depth qualitative interview was conducted with 100 primary family caregivers for PLwD in 2021 on care management during the COVID-19 pandemic. Watkins' rigorous and accelerated data reduction technique was used to analyze qualitative data through open and focused coding and identify themes specific to family caregiver's access to and use of community-based and health care services. Themes emerged regarding challenges and benefits of service use during the pandemic. Caregivers struggled with not being allowed to attend medical appointments with the PLwD or to speak confidentially with the physician over a PLwD's telehealth appointment. Caregivers felt physicians couldn't always read the care situation over telehealth, but appreciated not having to leave the house. Losing the consistency of in-home caregivers or respite programs put additional strain on caregivers, but many found virtual programming engaging. Grocery delivery/pickup was a new service used by many caregivers and found to be supportive of in-home care. As the pandemic evolves, finding ways to support caregivers through continued involvement in health care visits and as they access community services is critical to caregiver and PLwD health and well-being.